Promoting crop diversification in rice-based irrigation systems. Proceedings of the Second Progress Review and Coordination Workshop of the Research Network on Irrigation Management for Crop Diversification in Rice-Based Systems (IMCD), Yogyakarta, Indonesia, 9-12 September 1991 - Miranda, S.M.; Maglinao, Amado R. (International Irrigation Management Institute, 1993)
Country reports presented at the workshop discussing the relevant experiences on irrigation and irrigation management, irrigated rice-based farming and crop diversification, programs/strategies and problems related to promoting crop diversification, and linkages with national, regional and international agencies and institutions.